Determinants of Top Management Compensation: Explaining the Impact of Economic, Behavioral, and Strategic Constructs and the Moderating Effects of Industry - Rajagopalan, Nandini; Prescott, John E. (Journal of Management, 1990)
This study examined the main effects of economic, behavioral, and strategic constructs and their interactions in explaining variations in levels of top management cash compensation. Based on a sample of 226 top-level executives in 90 firms, the study also examined interactions between these constructs and industry structure across three diverse industry groups. Multiple regression analyses revealed several significant main effects for constructs drawn from each of the categories, but offered little support for interaction effects between categories. Moderated regression analysis indicated that industry structure has significant effects on the relationships between antecedent variables and compensation, but these effects are not pervasive. Finally, the study found that "high" diversifiers compensated significantly more than "low" diversifiers in the total sample and in two out of the three industry groups.